Application of supportive psychotherapy among COVID-19 positive patients - Yang Xiao; Yang Xiufang; Ma Xiaohong (Sichuan jingshen weisheng, 2021)
ObjectiveTo explore the role of supportive psychotherapy in mental health improvement of COVID-19 positive patients， and to provide references for the implementation of early psychological intervention measures in response to the sudden epidemic outburst， such as COVID-19.MethodsA total of 35 patients with severe COVID-19 admitted to ICU ward of Wuhan People’s Hospital from February 1 to March 1， 2020 were enrolled in this study. All the selected individuals received a 2-week supportive psychotherapy. Then Pittsburgh Sleep Quality Index （PSQI）， Patients’ Health Questionnaire Depression Scale-9 item （PHQ-9）， Generalized Anxiety Disorder Scale （GAD-7） and Social Support Rating Scale （SSRS） were used to evaluate the sleep quality， depression， anxiety and social support of participants at the baseline and the 2nd week of the intervention.ResultsInsomnia was detected in 32 patients （91.43%）， anxiety symptoms in 31 （88.57%）， depressive symptoms in 32 （91.43%）， and 29 patients （82.86%） reported feeling a lack of social support. After 2 weeks of intervention， the PSQI， GAD-7 and PHQ-9 scores decreased （t=5.272， 5.475， 4.621， P<0.01）， and SSRS score increased （t=-4.639， P<0.01）. After the intervention， the proportion of patients with insomnia， anxiety， depression and lack of social support was also decreased （χ2=18.714， 16.232， 16.970， 4.480， P<0.01）.ConclusionSupportive psychotherapy may ameliorate anxiety， depression and sleep quality in COVID-19 patients.